Construction of cell line stably expressing IBDV VP 2 protein mutants - SUN Jing; WEI Yong-wei; ZHANG Xiao-dong; YU Lian (浙江大学学报. 农业与生命科学版)
A couple of primers was designed on the base of VP2 gene sequence of infectious bursal disease virus (IBDV) HZ2 strain, and the VP2 gene was successfully cloned into eukaryotic expression vector pDsRed2-N1. Then, the recombinant plasmid pDsRed2-N1-VP2 was constructed. The 279 site and 284 site on VP2 protein were mutated singly or homeochronously through site-directed mutagenesis on the constructed vector pDsRed2-N1-VP2. By this way, three mutants of P279, P284 and PDA were constructed in next step. The Vero cell line stably expressing VP2 protein and this mutant were also constructed successfully on the base of P279, P284 and PDA by indirect immunofluorescence test. The recombination plasmid and cell line constructed lay the foundation on the deep research about the role and mechanism of 279 site and 284 site in virulence change and antigenic variation of IBDV, which also play a significant role in exploring more efficient and cheaper IBDV DNA vaccination.